PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TPS (THINK PAIR SHARE) UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS VII SMP NEGERI 6 KOTA BENGKULU - Renitasari, Renitasari (Program Studi S1 Pendidikan Matematika FKIP Universitas Bengkulu, 2018)
This study aims to improve student learning outcomes through the application of cooperative learning model of (think pair share) of class VII SMP Negeri 6 Kota Bengkulu. This research was an action research with 4 phases. There were planning, acting, observing, and reflecting. The samples of this research are the students in first grade B junior high school number 6 Bengkulu city. The total sample of this research was 22 students. The instrument of this research used of the students learning’s score. The students learning’s score can be improved by several ways; a) Train students to make material conclusions or add information using their own language. b) Provide guidance to students in understanding the problems that exist at the stage of think and pair. c) Provide reading assignments to students about the material learned at the next meeting so that the student have good initial knowledge in learning. Increased student learning outcomes can be seen from the increase in the average student score from cycle I to cycle III 67.86; 74.45; 83.80 with the percentage of classical learning completeness from cycle I to cycle III 45,45%; 50.00%; 81.82%.Key words: Think Pair Share, the students’ learning score.